スバールバル ショトウ ニーオルスン ニオケル タイキチュウ O_2/N_2 ヒ カンソク ノタメニ カイハツ サレタ コウセイド レンゾク ソクテイ システム ト ショキ カンソク ケッカ - 後藤, 大輔; ゴトウ, ダイスケ; 森本, 真司; モリモト, シンジ; 青木, 周司; アオキ, シュウジ; 中澤, 高清; ナカザワ, タカキヨ; Goto, Daisuke; Morimoto, Shinji; Aoki, Shuji; Nakazawa, Takakiyo (2013)
P(論文) スバールバル諸島ニーオルスンにおける大気中O_2/N_2 比の時間変動を明らかにするため,±4.0 per meg 以内の精度で連続測定できるシステムを新たに開発した.観測サイトが遠隔地にあることを考慮し,(1) インターネットを利用して日本からシステムを起動・停止できる,(2)システムから出力されるデータはインターネットを介して日本で監視・取得できる,(3)スターリングクーラーを利用した大気試料の除湿装置を開発し,水トラップの保守を自動化する,(4)CO_2 濃度も同時に測定できる,(5)標準ガスや参照ガスのシリンダーを交換することなく1 年間の連続測定を可能にするといった点に特に注意を払った.このシステムを用いた系統的観測を2012 年11 月8 日に開始した.観測開始後の1 カ月間に取得したデータを解析することによって,本システムの有効性を明らかにするとともに,観測された特徴的なO_2/N_2 比の時間変動について原因を考察した. With the aim of carrying out detailed monitoring of temporal variations in the atmospheric O_2/N_2 ratio at Ny-Alesund, Svalbard, we have developed a new highprecision continuous measurement system, with a precision of better than ±4.0 per meg, using a fuel-cell O_2 analyzer. Considering the remoteness of the observation site, special attention was paid to the measurement system, in that: (1) the system can be controlled remotely from Japan using the Internet; (2) all of the data output from the system can be monitored and collected in Japan via the Internet; (3) a specially designed water trap based on a Stirling cooler is employed to automate the removal of water vapor from the sample air; (4) the CO_2 concentration can also be measured; and (5) it is possible to operate the system for one year without having to manually replace the high-pressure cylinders of standard gas and reference air. Systematic observation of the atmospheric O_2/N_2 ratio using the newly developed measurement system began at the site on November 8, 2012. By analyzing the observational results obtained over the first month, the effectiveness of the measurement system was verified, and the causes of cha acteristic temporal variations in the observed atmospheric O_2/N_2 ratio were examined. departmental bulletin paper